BENTUK PENDIDIKAN KARAKTER DI KARATON KASUNANAN SURAKARTA BERBASIS AJARAN TRI HITA KARANA - Widhi Astuti (Widya Aksara, 2020)
Karaton kasunanan Surakarta which is located in Surakarta city. Precisely at the east end of Brigadier General Slamet Riyadi. The Surakarta kasunanan Palace was built at the initiative Susuhan Pakoe Boewono ll to move the Kartasura Palace which had been damage by the rebellion. According to spiritual experts Sala village is suitable for the establish of a new Karaton, and will be 200 years old. The prediction did indeed happen The Kasunanan Surakarta palace was inaugurated in 1745 and in 1945 the Karaton Kasunanan Surakarta no longer function as the center of government, now a culture preservation. All literary works, buildings and ceremonies of the Karaton Kasunanan Surakarta as a source of Javanese culture, As a noble culture heritage of java must be preserved, all are symbols that serve as a guide for life, material for character education for human life. Support of the preservation of Javanese culture are Susuhan Pakoe Boewono, all members of the Karaton and Abdi Dalem and who are loyal to the culture Kasunanan Karaton in Surakarta. In the discussion is to emphasize the teachings of Tri Hita Karana which is still applied in Karaton Kasunanan Surakarta. Hindu teaching teach three forms of good relationships to achieve harmony in life, namely the so-call Tri Hita Karana, humans with fellow humans and humans with nature. These three relationships can be found with in the Karaton Kasunanan Surakarta scope which also contains elements of education about God. Behavior that is completely immoral, orderly, polite, virtuous, smooth.